2007
DOI: 10.2307/25549740
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Correct Condom Use and Consistency of Use among Adolescents in Four Countries in Sub-Saharan Africa

Abstract: Using data from the 2004 National Adolescent Surveys, this paper undertook a detail analysis of knowledge of correct condom use and consistency of use, as well as their covariates, among adolescents in Burkina Faso, Ghana, Malawi and Uganda. The strongest predictor of knowledge of correct condom use among both male and female adolescents is exposure to a condom use demonstration. In Burkina Faso, Ghana and Uganda, adolescents who have seen a condom demonstration are 2 to 5 times as likely as those who have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 20 publications
(8 reference statements)
8
68
2
1
Order By: Relevance
“…and such youths in Sub-Saharan Africa still engage in risky sexual behavior. Studies have also documented that young people have concerns about condom safety and breakage, condom ineffectiveness, the negative effect of condom use on sexual enjoyment, the low quality of condoms especially those that are free and condom use signifying infidelity or having an STI [20]- [23]. The above results/findings call for a well-organized information, education and communication through peers to bring about behavioral change.…”
Section: Discussionmentioning
confidence: 99%
“…and such youths in Sub-Saharan Africa still engage in risky sexual behavior. Studies have also documented that young people have concerns about condom safety and breakage, condom ineffectiveness, the negative effect of condom use on sexual enjoyment, the low quality of condoms especially those that are free and condom use signifying infidelity or having an STI [20]- [23]. The above results/findings call for a well-organized information, education and communication through peers to bring about behavioral change.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of media penetration have been associated with emerging cultures of risk prevention through condoms among youth in South Africa, Burkina Faso, Ghana, Malawi and Uganda. 49,136 However, Eaton et al, 63 based on their work in South Africa, caution that media messages may be confusing and difficult to understand. In cultures where sex is not in the popular domain of discourse or communication, and different ethnic groups each have their own way of speaking about sexuality and condom use, it is difficult to craft messages that are readily and uniformly understood.…”
Section: Media Influencesmentioning
confidence: 99%
“…Most adolescents lack information on sexuality and contraception, as most of the education that is presented on this matter is limited (Arai 2003;Bankole, Ahmed, Ouedraogo, Neema & Konyani 2007). The study by Kaufman, De Wet and Stadler (2001) indicated that there was a slightly lower level of knowledge about modern methods of contraception amongst teenagers.…”
Section: Introduction Problem Statementmentioning
confidence: 99%
“…Morake (2011) indicated that in the reports of the Department of Health of the Limpopo Province, adolescents were reportedly not good contraceptive users, because they might not admit to being sexually active. Other studies reported that adolescents had inaccurate knowledge on the use of contraceptive (Bankole et al 2007). …”
Section: Introduction Problem Statementmentioning
confidence: 99%